Matrizes e suas possibilidades metodológicas no ensino médio: um estado da arte - Felippi, Luana Engeler (2024)
This research presents the state of the art over the last five years on the use of Mathematics teaching methodologies in relation to matrices. A study was conducted based on works selected from three research platforms: the PROFMAT dissertation bank, the ENEM annals on the SBEM website and the CAPES Portal. The selection of these works was carried out through the use of filters and careful reading, identifying the presence of expressions such as 'matrices', 'matrices teaching' and 'Mathematics teaching methodologies'. After selection, a process was carried out to identify the Mathematics teaching methodologies used in the context of the matrices. The research included 31 works that addressed some methodologies, such as history of mathematics, mathematical investigation, ethnomathematics, mathematical modeling, digital technologies and games. Among these, the use of technologies in teaching matrices stood out, being identified in 26 publications, representing 83.9% of the total. The main activities covered in the work using technology involve the use of applications, software and electronic spreadsheets to perform calculations with matrices, the use of video lessons and the construction of digital images.